Teaching Karl Rahner - O'Meara, Thomas F. (Philosophy & theology, 1998)
This essay, beginning with pastoral and theological reasons why Karl Rahner is still important fifteen years after his death, discusses how his theology figures explicitly in a graduate course, and implicitly in an undergraduate course. Special attention is paid to the transcendental, categorical and historical modalities of grace and revelation.